2017
DOI: 10.1186/s12882-017-0640-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate level and mortality in metformin-associated lactic acidosis requiring renal replacement therapy: a systematic review of case reports and case series

Abstract: BackgroundThe current practice concerning timing, mode, and dose of renal replacement therapy (RRT) in patients with metformin-associated lactic acidosis (MALA) with renal failure remains unknown. To investigate whether serum lactate level and prescription pattern of RRT are associated with mortality in patients with MALA requiring RRT.MethodsWe searched PubMed/Medline and EMBASE from inception to Sep 2014 and applied predetermined exclusion criteria. Case-level data including case’s demographics and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 32 publications
6
48
2
11
Order By: Relevance
“…Patients in the ECTR group were sicker than patients in the non-ECTR group considering the degree of lactic acidosis, kidney function, and vasopressor requirement while having a lower but not statistically different, mortality. As hyperlactatemia in general and in MALA patients is associated with increased mortality [8,11,[23][24][25], this at least comparable outcome suggests there might be a benefit for ECTR. This is also suggested by Peters et al [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the ECTR group were sicker than patients in the non-ECTR group considering the degree of lactic acidosis, kidney function, and vasopressor requirement while having a lower but not statistically different, mortality. As hyperlactatemia in general and in MALA patients is associated with increased mortality [8,11,[23][24][25], this at least comparable outcome suggests there might be a benefit for ECTR. This is also suggested by Peters et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…Calello et al [1] have not formulated a threshold for metformin serum concentration because at the time of formulation of these recommendations, there was much uncertainty regarding the value of metformin concentrations in relation to the prognosis and the limited availability of the metformin assays. Some studies have shown a correlation between metformin concentration and mortality [8,9,20] while others have not [17,21,25,26]. Despite the uncertainty concerning its prognostic value, measuring metformin serum concentrations could be of diagnostic value in MALA and may assist in its management [9,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Die Metformin-assoziierte Laktatazidose (MALA) ist ein schweres Krankheitsbild und wird definiert als eine arterielle Laktatkonzentration von ≥ 5 mmol/l und einem pH ≤ 7,35 in Assoziation mit der Einnahme von Metformin [1]. Pathophysiologisch ist sie bedingt durch einen erhöhten anaeroben Glukoseumsatz, insbesondere im Splanchnikusgebiet, mit inadäquater hepatischer Laktatelimination bei Nieren-/Leberversagen oder übermäßiger Bildung [2,3]. Der exakte zelluläre Mechanismus ist Gegenstand aktueller Forschung, jedoch scheint die Metformin-bedingte Hemmung von Komplex I der mitochondrialen Atmungskette von essenzieller Bedeutung [4].…”
Section: Definition Und Epidemiologieunclassified
“…Diese Unterscheidung ist jedoch unscharf und wird uneinheitlich angewandt. Die MALA hat eine Inzidenz von 1 bis 9 pro 100 000 Patientenjahren [6] und weist eine Mortalität zwischen 17 und 47 % auf [3,6,7]. Als prognoseverschlechternde Faktoren gelten das Ausmaß der Hyperlaktatämie und der Azidose [6], auch wenn dies nicht uniform akzeptiert ist [2,7].…”
Section: Definition Und Epidemiologieunclassified
See 1 more Smart Citation